The Impact Digital Marketing on Consumer Decisions in Choosing Educational Institutions Linked to Population Data - Firmansyah, Edy; Siregar, Ilhamsyah; Yusnandar, Yusnandar (Institute of Computer Science (IOCS), 2025)
This study's goal is to investigate the effects of digital marketing, specifically digital promotion, website quality, and interesting content on consumer decisions in selecting vocational education institutions in North Sumatra Province, Indonesia. Despite the increasing use of digital platforms by schools, student enrollment rates, particularly in vocational schools, remain low. This research addresses this gap by examining how digital marketing components affect parental decision-making as key consumers in education. Using a descriptive quantitative method that uses analysis of multiple linear regression, the study collected primary data from 90 respondents which parents of prospective vocational school students through uses purposive sampling across four regions, Medan, Deli Serdang, Serdang Bedagai, and Langkat. Data were obtained via questionnaires distributed through WhatsApp and analyzed Using tests of classical assumption, regression analysis, and validity and reliability. The outcomes for this research indicate that digital promotion and interesting content significantly to influence consumer decisions, while website quality does not have a significant individual effect. The regression model explains 68.4% of the variation in decision making. This study contributes both theoretically and practically by offering insights into effective digital marketing strategies for educational institutions to increase enrollment and improve digital communication with target audiences.